How spirituality strengthens community resilience to flood disasters - Setioputro, Baskoro; Haristiani, Ruris; Iksafani, Moh Afif Jakaria; Yunanto, Rismawan Adi (Jurnal Penelitian, 2024)
Flood is one of the natural disasters that often occurs in Indonesia. Floods that threaten and disrupt people's lives cause casualties, environmental damage, loss of property, and psychological impacts. The community's ability to deal with disasters well through the process of adaptation and maintaining self-functions so that they return to their original state before the disaster occurs. Spirituality has an important role in forming a resilient individual. Individuals with good spirituality have a strong relationship with their God, fellow human beings, and even with themselves. The purpose of this study was to determine the relationship between spirituality and community resilience to floods in Wonoasri Village, Tempurejo District, Jember. The independent variable of this research is spirituality and the dependent variable is disaster resilience. This research is a correlational study with a cross-sectional approach. Sampling using the g-power application with the results of 193 respondents. Data collection using the DSES questionnaire and resilience questionnaire. Data analysis used Kendall's Tau C test with a p-value <0.05. The results of this study indicate a positive relationship between the two variables. There is a relationship between spirituality and resilience to floods in Wonoasri Village, Tempurejo Jember district (Î± = 0.000 or Î± < 0.05. Correlation coefficient 0.279). This research shows that the higher the level of spirituality, the higher the level of resilience possessed.